Materiality, Tactility, and Artmaking: An Exploration of Diasporic Trauma through Creative Pedagogy - Moussavi, Yasaman (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2024)
This paper explores the role of artmaking and tactile materials in learning and overcoming “stuckness” (Hage, 2009; Cangia, 2021), a state of discomfort caused by mobility constraints through an autobiographical approach. I explore how the tactile material artmaking processes can generate educational sites, and serve as a pathway to process trauma. The findings of this paper can empower learners to harness the therapeutic potential of artmaking, fostering resilience and growth through the creative process.